Abstracts of Symposium I: Stable Coronary Artery Disease: The Stable Plaque - Symposium I: Stable Coronary Artery Disease: The Stable Plaque (ACI (Acta Cardiologia Indonesiana), 2018)
Abstracts of Symposium I: Stable Coronary Artery Disease: The Stable Plaque